2001
DOI: 10.1002/pros.1077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bowman–Birk inhibitor concentrate (BBIC) in patients with benign prostatic hyperplasia*†

Abstract: The data obtained in this trial, particularly the data suggesting that BBIC treatment may lead to reduced serum PSA levels and reduced prostate volumes, suggest that a Phase II clinical trial of BBIC for the therapy of BPH is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Although BBI languished for many years as an anti-nutrient, clinical trials have shown that BBI has now become an important protein for disease prevention (Kennedy 1998;Armstrong et al 2000a, b;Meyskens 2001;Tolcher et al 2001). Extensive in-vitro toxicity and clinical studies of BBI at levels normally found in food and at higher levels have confirmed that BBI is safe (Kennedy 1998;Malkowicz et al 2001) and is now considered a functional food (Losso et al 2004). Therefore instead of using intensive heat treatment to completely destroy trypsin inhibitor and in turn BBI, optimal heat during processing retaining 20-25 % of the complex is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Although BBI languished for many years as an anti-nutrient, clinical trials have shown that BBI has now become an important protein for disease prevention (Kennedy 1998;Armstrong et al 2000a, b;Meyskens 2001;Tolcher et al 2001). Extensive in-vitro toxicity and clinical studies of BBI at levels normally found in food and at higher levels have confirmed that BBI is safe (Kennedy 1998;Malkowicz et al 2001) and is now considered a functional food (Losso et al 2004). Therefore instead of using intensive heat treatment to completely destroy trypsin inhibitor and in turn BBI, optimal heat during processing retaining 20-25 % of the complex is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…BBI derived from soybeans has been studied extensively as an anti-carcinogenic protease inhibitor, as many protease inhibitors suppress carcinogenesis (19). Several studies have demonstrated the efficacy of BBI against tumors in animal models (9,11,20) and in human Phase IIa clinical trials (12,14). BBI is the only protease inhibitor derived from soybeans that possesses a chymotrypsin inhibitory activity (21).…”
Section: Discussionmentioning
confidence: 99%
“…BBI concentrate (BBIC) is an extract of soybeans enriched in BBI, which has attenuated trypsin-inhibitory activity (8 (12). In a Phase IIa trial (13,14), changes in protease activity in oral mucosal cells after BBIC treatment correlated with changes in protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, BBIC has prevented the growth of prostate tumors in transgenic rats developing adenocarcinoma, most likely as a consequence of its antiproliferative activity via induction of connexin 43 expression [76,77]. In humans, a doubleblind, randomized, phase I trial was carried out in nineteen male subjects with benign prostatic hyperplasia, which is a precursor condition for prostate cancer, and lower urinary tract symptoms [5]. In this study, the authors demonstrated that BBIC treatment for six months reduced levels of prostate-specific antigen (PSA), a clinical marker for prostate cancer, and prostate volume in patients.…”
Section: Prostate Cancermentioning
confidence: 99%
“…In light of the Food and Drug Administration (FDA) approval for trials of Bowman-Birk inhibitors (BBI) concentrate (BBIC), a protein extract of soybean (Glycine max) enriched in BBI, as an 'Investigational New Drug', human trials have been completed in patients with benign prostatic hyperplasia [5], oral leukoplakia [6][7][8] and ulcerative colitis [9] (Table 1). Although, in most of these cases, the intrinsic ability of BBI to inhibit serine proteases has been related to beneficial health properties, the mechanisms of action and the identity of their therapeutic targets are largely unknown.…”
Section: Introductionmentioning
confidence: 99%